Analisis Perbandingan Sistem Inferensi Fuzzy Mamdani Dan Fuzzy Sugeono Dalam Menentukan Siswa Terbaik - Helmi Fauzi Siregar; K Kartika (LPPM STIKOM Tunas Bangsa, 2023)
In the process of selecting the best students, there are several indicators that are also important factors that is grades, absenteeism, academic and non-academic achievements. The purpose of this study is to be able to apply an information system comparison application in determining the best students at SMA Negeri 1 Aek Kuo. The data used in this study are student data, test score data, attendance attendance data and academic and non-academic achievement data. The results of the assessment obtained have the same decision results, from this test it can be seen that the calculation results of a student with the highest score using the Mamdani method are Tira Dwi Fitri Br Naibaho with a score of 70 while the Sugeno method is Tira Dwi Fitri Br Naibaho with a value of 39. This application later it can be accessed online and can be accessed anywhere and anytime